2018
DOI: 10.1038/s41419-018-0838-9
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of homeodomain-interacting protein kinase 2 (HIPK2) attenuates sepsis-mediated liver injury by restoring autophagy

Abstract: Sepsis is the leading cause of death in intensive care units worldwide. Autophagy has recently been shown to protect against sepsis-induced liver injury. Here, we investigated the roles of homeodomain-interacting protein kinase 2 (HIPK2) in the molecular mechanism of sepsis-induced liver injury. HIPK2 expression was reduced in sepsis-induced liver injury, and HIPK2 overexpression increased the survival rate and improved caecal ligation and puncture (CLP)-induced liver injury by reducing serum and liver asparta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 75 publications
(99 reference statements)
2
21
0
Order By: Relevance
“…The authors confirm that the animals received humane care and that all animal experiments were performed in accordance with the relevant guidelines and regulations (4). The CLP mouse model was established as previously reported (16). Mice were administered with sophocarpine through oral gavage for 3 days.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…The authors confirm that the animals received humane care and that all animal experiments were performed in accordance with the relevant guidelines and regulations (4). The CLP mouse model was established as previously reported (16). Mice were administered with sophocarpine through oral gavage for 3 days.…”
Section: Methodsmentioning
confidence: 94%
“…The mice were sacrificed on day 6 and blood and liver samples were obtained. Bafilomycin A (10 mg/kg) ( 16 ) or MG-132 (10 µg/kg; MedChemExpress), according to previously proposed dosages ( 17 ), were injected intraperitoneally 2 h before the CLP procedure (these inhibitor is administered at the operation day). After the CLP procedure, mice were administered sophocarpine for the following 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…Autophagy is the main specific degradation mechanism for MBR removal (Pohl and Jentsch, 2009;Kuo et al, 2011;Isakson et al, 2013). Recently, exogenous expression of HIPK2 in primary mouse hepatocytes has been shown to stimulate autophagy (Jiang et al, 2018). Thus, we asked whether HIPK2 might have a role in mediating MBR autophagic degradation.…”
Section: Hipk2 Regulates Mbr Removal Through Autophagy-mediated Degramentioning
confidence: 99%
“…Each of these steps can be dynamically regulated via a complex network of autophagy-relevant proteins and by posttranslational modifiers including kinases (Stork et al, 2012). It has been suggested that HIPK2 overexpression promotes phagophore expansion and increases mature autophagosome formation in liver sepsis (Jiang et al, 2018). In Caenorhabditis elegans, the HIPK-family orthologous HPK-1 is required for inducing autophagosome formation and autophagy gene expression in response to dietary restriction or TORC1 inactivation (Das et al, 2017).…”
Section: Figure 4 | Continuedmentioning
confidence: 99%
“…Moreover, deposition of extracellular matrix and decreased crystallin protein expression by the keratocytes causes scar formation and reduces corneal transparency [8]. Therefore, effective methods are necessary to inhibit Homeodomain-interacting protein kinase 2 (HIPK2) is a serine/threonine kinase that is primarily located in the nucleus of eukaryotic cells [23]. HIPK2 is a pro-fibrotic gene that plays an important role in kidney fibrosis [24].…”
Section: Introductionmentioning
confidence: 99%